Let love find you [large type] - Lindsey, Johanna (Thorndike Press large print core series., 2012)
"London society has its very own Cupid. Renowned horse breeder and occasional matchmaker Devin Baldwin pairs eligible young ladies with suitable gentlemen based on his theory of animal magnetism. Amanda Locke, the daughter of a duke, is everything a nobleman could desire, yet she enters her third Season still searching for a match. When an earl passionate about horses becomes the target of her husband hunt, Amanda knows it's time to overcome her fear of riding. With her sister-in-law Ophelia hastening the romance along by arranging riding lessons, Amanda is soon taking instruction from infuriating Devin Baldwin. Astonishingly, in her daily encounters with Devin, Amanda experiences passion for the first time" -- Cover verso.